(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Agriculture and manufacturing industry are the major producing sectors of Indian economy. Agriculture sector plays a major role in the overall development of the country. Indian agriculture sector contributes around 18 of India’s Gross Domestic Product (GDP) and engages around 50 of the population of the country. Karnataka is India’s 8th largest state in geographical area. Agriculture is the major occupation for a majority of the rural population. Karnataka agriculture sector contribute around 16 (2011-12) to the state GSDP. The contribution to GDP from agriculture sector is decreasing there is significant growth in manufacturing and services sector. Service sector alone contributes more than 50 to GDP. Growth in manufacturing sector and service sector is contributing for the better living conditions and life style of urban population. The agriculture is the major occupation for a majority of rural population, but growth in agriculture sector is lack in providing better living conditions and life style to rural population. The result is imbalance in development between urban and rural. In keeping these imbalances in mind, to achieve balance economic development, to take advantage of changing life style of urban population and changing socio-economic environment, it is essential to shift from business to agribusiness and promote Agripreneurship. This paper focused on the concept of Agripreneurship, agribusiness, Agripreneurship development, Agripreneurship in Karnataka, the challenges and opportunities of Agripreneurs.